Electrical Conductivity and Dielectric Properties of Bulk Glass V2O5 (ZnO, PbO) SrO FeO. (24th May 2011) - Aziz, M. S.; Mostafa, A. G.; Youssef, A. M.; Youssif, S. M. S.
Abstract : The AC conductivity and dielectric parameters of the glassy system of (70- x ) V2 O5 ·  x (Zn/Pb)· 10SrO · 20FeO ( x = 0, 5, 10, and 15) glasses have been investigated. The frequency and temperature dependence of dielectric constant ( ε ′) and dielectric loss ( ε ′′) is studied in the frequency range 100 Hz–5 MHz and in the temperature range 300–460 K. Dielectric dispersion is observed in all samples as Zn/Pb increase content in the (70- x )V2 O5 ·  x (Zn/Pb)·10SrO·20FeO systems. These results are explained on the basis of a Debye-type relaxation. It is also observed that the activation energy increases on increasing the Zn/Pb contents in this system.